PERANCANGAN SISTEM EKSTRAKURIKULER PADA SMP NU AL MA’RUF KUDUS BERBASIS WEB DAN SMS GATEWAY - Adhita Arif Setyawan; Devy Octaviana; Yonan Heriyanto (POLITEKNIK PIKSI GANESHA, 2021)
This Web Based Analysis and Design of the Extracurricular System at SMP NU Al Ma'ruf Kudus discusses the data collection system for extracurricular students, extracurricular attendance, extracurricular assessments and extracurricular reports. Where the admin will input student data according to the NIS they have, so that students can register for extracurricular activities and the supervisor coordinator can conduct assessments and produce reports that are received by the principal. This system also provides an SMS Gateway for information via cellular. With this system, the supervisor coordinator can record extracurricular assessments and produce printable extracurricular report output. The final result of the design resulted in an Extracurricular System Application at SMP NU Al Ma'ruf Kudus Web-Based and SMS Gateway.